SOIL DISTRIBUTION IN CRNA RIVER BASIN AND ITS IMPORTANCE FOR AGRICULTURAL PRODUCTION - Mile MARKOSKI, Tatjana MITKOVA, Vjekoslav TANASKOVIK, Velibor SPALEVIC and Rajko NOVICEVIC (Agriculture & Forestry, Vol. 67 Issue 1: 125-138, 2021, 2021)
This paper is a result of many years of field and laboratory research of the soils in Crna River Basin, spread out on 497 514,81 ha, with the altitudes ranging from 150 to 2601 m above sea level with the main goal of gaining better understanding of the productive capacities of soils and soil conservation measures for their improvement. The catchment area of the Crna River is a spatial area that extends in two states in the southwest of the Republic of North Macedonia and the northern part of the Republic of Greece. The filed research of the soils and preparation of soil samples has been done according to ISO 10381-1 and ISO 10381-2 protocols. Soil samples were analysed in the laboratory: hygroscopic moisture; mechanical composition; pH of the soil solution; humus content and total nitrogen; content of carbonates; available nutrients P2O5 and K2O. The mechanical composition and chemical properties of the soils were determined by standard methods. Physical-geographical conditions of the studied area are heterogeneous, with numerous relief forms; different expositions and inclinations, and with great differences of altitude. There are several geological formations of a very heterogeneous petrographic-mineralogical composition and climate-vegetation zones. Long-term effects of human participation should also be noted. The vast diversity of the factors required for soil formation in the catchment area of the Crna River are the reason for the formation of many different soil types as well as the lower taxonomic units. There are 14 (fourteen) different soil types distributed in the Crna River Basin together with a considerable amount of subtypes, varieties and forms. The most significant soil types are: Fluvisol and Cambisol. These types of soils are characterized by different properties (chemical, physical, physical-mechanical and productive). Therefore, they have varied effects on agricultural production (field crop, viticulture and fruit production). The aim of this research was to present combined measures of soil conservation for soils from mountain terrains, lake terraces and undulating-hilly terrains, including from sloping terrains and from plain terrains, based on the research that was implemented.
Keywords: Soil types, Crna River Basin, Agricultural production